2022
DOI: 10.3390/ijerph19105924
|View full text |Cite
|
Sign up to set email alerts
|

Dark Side or Bright Side: The Impact of Alcohol Drinking on the Trust of Chinese Rural Residents

Abstract: Existing studies have explored the causal effect of social capital on harmful drinking, while the effect of drinking habits on trust is scant. In China, drinking rituals and drinking culture are considered important ways of promoting social interaction and trust, especially in rural areas where traditional culture is stronger. Based on a field survey in rural China in 2019, this paper explores the relationship between drinking habits and trust. First, we found a negative relationship between drinking habits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…For instance, in a previously documented systematic review by our team, it was revealed there is a strong correlation between alcohol consumption patterns and age, proximity to alcohol outlets, familial backgrounds, socioeconomic backgrounds, and religious influences [7]. Similarly, other recent records documented the social determinants of alcohol use and its consequences among communities [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, in a previously documented systematic review by our team, it was revealed there is a strong correlation between alcohol consumption patterns and age, proximity to alcohol outlets, familial backgrounds, socioeconomic backgrounds, and religious influences [7]. Similarly, other recent records documented the social determinants of alcohol use and its consequences among communities [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 88%
“…To evaluate the performance of the quantification algorithm, the following performance metrics were used: (1) mean square error (MSE), ( 2) root mean square error (RMSE), (3) mean absolute error (MAE), ( 4) the coefficient of determination (R 2 ), (5) the accuracy percentage (Accuracy%), ( 6) the standard deviation, and ( 7) the relative standard deviation (%RSD), shown in Equations ( 5)- (11), respectively. The values of BrAC e and BrAC a refer to the predicted BrAC obtained from the algorithm and the actual BrAC, respectively.…”
Section: Experimental Setup and Performance Evaluationmentioning
confidence: 99%